Awareness of Listeriosis and Methylmercury toxicity public health recommendations and diet during pregnancy. Issue 1 (February 2019) - Zhou, Shao Jia; Greco, Rebecca L.; Grivell, Rosalie; Louise, Jennie; Deussen, Andrea; Dodd, Jodie; Moran, Lisa J.
Abstract: Background: Awareness of Listeriosis and Methylmercury toxicity recommendations are associated with decreased intake of high-risk foods. Whether awareness of the recommendations affect dietary quality of pregnant women in Australian is unknown. Aim: To evaluate awareness of Listeriosis and Methylmercury toxicity recommendations during pregnancy and its impact on dietary quality. Methods: Pregnant women (n = 81) were recruited from antenatal clinics. Awareness of Listeriosis and Methylmercury toxicity recommendations and high-risk foods consumption were assessed via questionnaire at 10–23 weeks gestation. Diet quality was measured using the 2005 Healthy Eating Index using a validated food frequency questionnaire at 10–23 and 34–36 weeks gestation. Findings: A higher proportion of women were aware of Methylmercury toxicity compared with Listeriosis recommendations (75.3 vs. 59.2%, p < 0.001). The proportion of women who decreased or avoided consumption of certain high-risk Listeriosis foods were higher in those who were aware compared with those who were unaware of Listeriosis recommendations [raw fish (96.0 vs 69.2%, p = 0.046), soft-serve ice cream (93.9 vs 58.3%, p = 0.004) and alfalfa/bean sprouts (68.7 vs 28.5%, p = 0.006)]. A large proportion of women (96.8%) met recommendations for limiting consumption of high Methylmercury fish. There was no difference in the change in dietary quality over pregnancy regardless of women's awareness of the recommendations. Discussion and conclusions: Awareness of Listeriosis and Methylmercury toxicity recommendations has little impact on dietary quality of pregnant women in this small study. Further research in a large representative population of pregnant women is needed to confirm our findings and to optimise dietary quality during pregnancy.